The Journal Of Jedediah Barstow An Emigrant On The Oregon Trail - Levine, Ellen (New York Scholastic, 2002)
In his 1845 diary, thirteen-year-old orphan jedediah describes his wagon train journey to oregon, in which he confronts rivers and sandy plains, bears and rattlesnakes, and the challenges of living with his fellow travelers
American Corner
Includes historical notes
11
Keywords: English Fiction; English Stories